2018
DOI: 10.5057/isase.2018-c000016
|View full text |Cite
|
Sign up to set email alerts
|

Study of QOL Assessment Management Application

Abstract: NCCN guidelines recommend conducting QOL assessments that display the score of a patient's quality of life, in addition tousing common assessment methods that simply diagnose the patient's medical conditions. Despite the effectiveness of these methods in determining the QOL for cancer patients, their paper answer sheets have always had a fixed format. As a result, there has been almost no progress in the efforts to digitize the questionnaires to effectively manage data, and clinicians have been required to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Being a barometer of the patient's QOL, EORTC QLQ-C30 (C30) was normally used and a camera was used for data entry to see how effective it was. The trial showed that it reduced the burden on the clinical staff for entering and analyzing data [3].…”
Section: Introductionmentioning
confidence: 99%
“…Being a barometer of the patient's QOL, EORTC QLQ-C30 (C30) was normally used and a camera was used for data entry to see how effective it was. The trial showed that it reduced the burden on the clinical staff for entering and analyzing data [3].…”
Section: Introductionmentioning
confidence: 99%